Disentangling the numbers behind agriculture-driven tropical deforestation - Pendrill, Florence; Gardner, Toby A.; Meyfroidt, Patrick; Adams, Justin; Azevedo, Tasso; Bastos Lima, Mairon G.; Baumann, Matthias; Curtis, Philip G.; Sy, Veronique de; Garrett, Rachael; Godar, Javier; Dow Goldman, Elizabeth; et al. (American Association for the Advancement of Science, 2022)
Agricultural expansion is recognized as a major driver of forest loss in the tropics. However, accurate data on the links between agriculture and tropical deforestation are lacking. Pendrill et al. synthesized existing research and datasets to quantify the extent to which tropical deforestation from 2011 to 2015 was associated with agriculture. They estimated that at least 90% of deforested land occurred in landscapes where agriculture drove forest loss, but only about half was converted into productive agricultural land. Data availability and trends vary across regions, suggesting complex links between agriculture and forest loss. —BEL